Analysis of energy consumption in lowland rice-based cropping system of Malaysia - Chan Chee Wan; Wan Ishak bin Wan Ismail; Azmi Yahya; Sahr Marvin Bockari-Gevao (Songklanakarin Journal of Science and Technology (SJST), 2005)
Sufficient energy is needed in the right form and at the right time for adequate crop production. One way to optimize energy consumption in agriculture is to determine the efficiency of methods and techniques used. With the current increase in world population, energy consumption needs effective planning. That is, the input elements need to be identified in order to prescribe the most efficient methods for controlling them. This study was undertaken in order to determine the direct and indirect energy consumption of field operations in a lowland rice production system of Malaysia. Field time, fuel and other energy requirements were measured for the tillage, planting, fertilizing, spraying and harvesting operations performed. Energy analysis carried out revealed the highest average operational energy consumption was for tillage (1747.33 MJ ha-1) which accounted for about 48.6% of the total operational energy consumption (3595.87 MJ ha-1), followed by harvesting (1171.44 MJ ha-1, 32.6%) and planting (562.91 MJ ha-1, 15.7%). Fertilizing and pesticide spraying did not make any significant contributions to the operational energy consumption. Based on energy sources, fuel was the main consumer of direct energy with 2717.82 MJha-1 (22.2%), and fertilizer recording the highest indirect energy consumption of 7721.03 MJha-1 (63.2%). Human labour, pesticides, seeds and indirect energy for machinery use had marginal importance, contributing only 0.2%, 0.6%, 6.8% and 6.9%, respectively to the total energy consumption (12225.97 MJha-1). Average grain yield was 6470.8 kg ha-1, representing energy output of 108321.75 MJha-1, that is, 96095.78 MJ net energy gain or 8.86 MJ output per MJ input. Energy input per kilogram grain yield was 1.89 MJkg-1. The results of the study indicate energy gain in the lowland rice production system of Malaysia.